Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Import Smarphone Brand Samsung (Studi Kasus Mahasiswa Institut Stiami Kampus C Jakarta) - Iqna Tulhanifah; Bertadi Nurseno (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to measure how much Price and Product Quality influence the Decision of college students for purchasing Samsung Smartphones at STIAMI Institute, campus C Jakarta. The research method we used, is the descriptive quantitative research method. Also, for the sampling technique, we apply the Probability sampling technique with the Simple Random Sampling method. The number of samples in this study was 87 respondents. Then the data is processed by the Multiple Linear Regression Analysis method. Lastly, the results of this study indicate that price and product quality have a positive and significant influence on purchasing decisions.